From the Pentagram to the Page: 'Compositio' and 'Variatio' in «Una ofrenda musical», by Luis Sagasti (Castilla. Estudios de Literatura, 2018)
Una ofrenda musical, by Luis Sagasti, published in 2017, constitutes a discursive artefact in line with the most experimental literature in Spanish. The work supposes the transcription in literary code of a musical piece, Goldberg Variations by Johan Sebastian Bach. This paper aims to realize a first approach, from the interartistic studies perspective, to the musical-literary strategies of composition, to the discursive hybridism and to the presence of music as a structure and theme to transit between the sound and the silence of a contrapuntal narrative.
Keywords: Luis Sagasti; Argentine literature; current literature; interartistic relations; music and literature